THE MAIN CHALLENGES AND PROSPECTS OF TRANSPORT LOGISTICS DEVELOPMENT IN THE CONDITIONS OF WAR - Mykhailyk, N. I. (The actual problems of regional economy development, 2024)
The article is devoted to the topic of challenges and prospects for the transport logistics development in Ukraine in the conditions of military invasion, on the basis of which the study purpose was formed, which consists in conducting a current state analysis of transport logistics and determining the development directions of the freight transportation market in conditions war in order to increase the country's logistics industry competitiveness. To achieve the set goal, a number of tasks were set and solved. The changes analysis that occurred in the freight transportation market of Ukraine as a result of the rf full-scale invasion was carried out and the key ones were highlighted: personnel problems, difficulties in organizing transportation, rising fuel prices and energy problems, as well as blocking the grain corridor and western borders. The problems in the freight transportation market by types of transport, which caused the above-mentioned changes, were analyzed and structured, and solving ways and minimizing the impact of them were formed. The main trends and directions of the transport logistics development in the martial law conditions to ensure the stability and profitability of the country's economy are highlighted, including investments in projects for the carrier market, the highways development and euro rails construction, an increase in the checkpoints number, digitization document flow digitization, etc. To implement the set tasks, general logical methods of analysis and synthesis were applied, as well as the method of generalization in forming the main of transport logistics development directions of Ukraine. The conclusions emphasize the adaptability transport logistics to modern uncertainty conditions, reorientation and search for new ways by carriers to ensure the stability and profitability of the country's economic development. The prospects for further scientific research on this topic were the study of the dynamics changes in the structure of freight transportation by types of transport after the implementation and realization of the proposed ways of solving existing problems in the industry and conducting general research of the freight transportation industry by interviewing managers of transport enterprises.